Analysis of the Use of Push Up Board Aids as an Alternative Exercise for Biceps and Triceps Brachii Muscles in the Kediri Regency Karate Sports Branch - Arismanda, Ivona Varella Putri; Pratama, Budiman Agung; Muharram, Nur Ahmad; Herpandika, Reo Prasetiyo (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2025)
In the sport of karate there are punching movements that center on muscle strength in athletes. To get the maximum blow, proper training is needed on the muscles, the imposition of muscles for this blow movement on the biceps and triceps brachii muscles. There are innovative tools that can be used for alternative training for karateka athletes, namely the push up board tool that has been developed according to the needs of karate athletes. This research was conducted with the aim of knowing the attractiveness, safety and feasibility of push up board aids to help karate athletes train the biceps and triceps bracii muscles as an alternative to karate athletes' punch training. This research uses descriptive Quantitative research methods. The data collection technique used in this quantitative research is by direct observation and distributing questionnaires. The results obtained in this study are a percentage of 51.4% based on trials on respondents and declared “Worthy”.